Recirculation and Residency of T Cells and Tregs: Lessons Learnt in Anacapri - Piconese, Silvia; Campello, Silvia; Natalini, Ambra (Frontiers in Immunology, 2020)
“Location location location”: according to this mantra, the place where living beings settle has a key impact on the success of their activities; in turn, the populating entities can in many ways modify their environment. This idea is becoming more and more true for T cells: their ability to recirculate throughout blood or lymph, or to stably reside in certain tissues, turns out to determine immunity to pathogens and tumors. If location actually matters also for human beings, the inspiring environment of Capri island may have contributed to the success of the EFIS-EJI Ruggero Ceppellini Advanced School of Immunology about “T cell memory”, held in Anacapri from 12 to 15 October 2018. In this minireview, we would like to highlight some novel concepts about T cell migration and residency, and discuss their implications in relation with recent advances in the field: i) the compartmentalization and cell cycle entry of T cells during activation; ii) the role of mitochondrial metabolism in T cell movement; iii) the residency of regulatory T cells.